The Influence of Transformational Leadership and Competence on Motivation and Its Impact on Employee Performance - Dini Ayu Nur Azizah; Dea Dwi Pratiwi; Bachrudin Syahroni; Moh Yudi Mahadianto (Journal Research of Social Science, Economics, and Management, 2025)
In the era of globalization, optimizing human resources is critical for organizational success, particularly in public services like PDAM Tirta Jati Cirebon Regency, where leadership and competence gaps hinder performance. This study investigates how transformational leadership and competence affect employee performance, with motivation as a mediator, addressing inconsistencies in prior researc. Using a quantitative associative approach, data from 72 employees were analyzed via PLS-SEM. Results reveal that transformational leadership significantly boosts both motivation and performance (T = 6.778, p = 0.000; T = 3.722, p = 0.000), while competence enhances motivation (T = 3.072, p = 0.002) but only indirectly impacts performance through motivation (T = 2.536, p = 0.012). Notably, motivation fully mediates the leadership-performance link, a finding that refines existing model. The study underscores the need for leadership development programs and competency-based training in public sector HR strategies, offering actionable insights to bridge theory-practice gaps in similar contexts.